The nation, Europe, and the world : textbooks and curricula in transition - Schissler, Hanna; Nuhoğlu Soysal, Yasemin (Berghahn Books, 2005)
Textbooks in history, geography and the social sciences provide important insights into the ways in which nation-states project themselves. Based on case studies of France, Germany, the Netherlands, Spain, Greece, Turkey Bulgaria, Russia, and the United States, this volume shows the role that concepts of space and time play in the narration of 'our country' and the wider world in which it is located. It explores ways in which in western European countries the nation is reinterpreted through European lenses to replace national approaches in the writing of history. On the other hand, in an effort to overcome Eurocentric views, 'world history' has gained prominence in the United States. Yet again, East European countries, coming recently out of a transnational political union, have their own issues with the concept of nation to contend with. These recent developments in the field of textbooks and curricula open up new and fascinating perspectives on the changing patterns of the re-positioning process of nation-states in West as well as Eastern Europe and the United States in an age of growing importance of transnational organizations and globalization.